2020
DOI: 10.3390/s20174738
|View full text |Cite
|
Sign up to set email alerts
|

Impedimetric Determination of Kanamycin in Milk with Aptasensor Based on Carbon Black-Oligolactide Composite

Abstract: The determination of antibiotics in food is important due to their negative effect on human health related to antimicrobial resistance problem, renal toxicity, and allergic effects. We propose an impedimetric aptasensor for the determination of kanamycin A (KANA), which was assembled on the glassy carbon electrode by the deposition of carbon black in a chitosan matrix followed by carbodiimide binding of aminated aptamer mixed with oligolactide derivative of thiacalix[4]arene in a cone configuration. The assemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 50 publications
0
7
0
1
Order By: Relevance
“…A comparison between determinations of KANA using different sensors was investigated and is shown in Table 1. It was found that the LOD calculated using the proposed sensor (0.161 nM) is the lowest among those obtained by surface plasmon resonance using a molecularly imprinted polymer (LOD in milk is 43.3 nM and honey is 12.0 nM), 26 ESI using MIP/GO/Ppy (5.0 nM), 27 DPV using MMIPs/MGCE (4.88 nM), 28 DPV using Apt/Co/Ni-Bio-MOF and Au-doped coral-like ZrO 2 (37 nM), 35 EIS using Apt/CB/CHIT/GCE (0.3 nM), 36 SWV using UiO-66-NH 2 /MCA/MWCNT@rGONR/GCE (13.0 nM), 37 DPV using Fc/β-CD-SH/Au@Fe 3 O 4 /GCE (1.87 nM), 38 DPV using Apt/ hemin-rGO-cMWCNTs/GCE (0.36 nM), 39 and colorimetry using the peroxidase-like activity of oxygen-terminated few-layered Ti 3 C 2 Tx MXene (15.28 nM). 40 In conclusion, the proposed sensor shows many advantages over other reported sensors for the deter-mination of KANA including the lowest detection limit, a wide linear range, and cost-effectiveness.…”
Section: Analytical Performance Of the Kana-mip/cpementioning
confidence: 99%
“…A comparison between determinations of KANA using different sensors was investigated and is shown in Table 1. It was found that the LOD calculated using the proposed sensor (0.161 nM) is the lowest among those obtained by surface plasmon resonance using a molecularly imprinted polymer (LOD in milk is 43.3 nM and honey is 12.0 nM), 26 ESI using MIP/GO/Ppy (5.0 nM), 27 DPV using MMIPs/MGCE (4.88 nM), 28 DPV using Apt/Co/Ni-Bio-MOF and Au-doped coral-like ZrO 2 (37 nM), 35 EIS using Apt/CB/CHIT/GCE (0.3 nM), 36 SWV using UiO-66-NH 2 /MCA/MWCNT@rGONR/GCE (13.0 nM), 37 DPV using Fc/β-CD-SH/Au@Fe 3 O 4 /GCE (1.87 nM), 38 DPV using Apt/ hemin-rGO-cMWCNTs/GCE (0.36 nM), 39 and colorimetry using the peroxidase-like activity of oxygen-terminated few-layered Ti 3 C 2 Tx MXene (15.28 nM). 40 In conclusion, the proposed sensor shows many advantages over other reported sensors for the deter-mination of KANA including the lowest detection limit, a wide linear range, and cost-effectiveness.…”
Section: Analytical Performance Of the Kana-mip/cpementioning
confidence: 99%
“…There is evidence that consuming food containing residues of this drug may result in serious side effects, including loss of hearing, nephrotoxicity, and antibiotic resistance [ 63 ]. The maximum residue limit (MRL) of kanamycin in milk has been set at 150 μg kg −1 in the EU and 200 μg kg −1 in China [ 64 , 219 ]. Several electrochemical aptasensing assays have been reported in the last years for kanamycin detection in milk samples [ 24 , 63 , 219 , 220 ].…”
Section: Electrochemical Aptasensors Developed Using Aryldiazonium Chemistry For Food Safety Monitoring Applicationsmentioning
confidence: 99%
“…The maximum residue limit (MRL) of kanamycin in milk has been set at 150 μg kg −1 in the EU and 200 μg kg −1 in China [ 64 , 219 ]. Several electrochemical aptasensing assays have been reported in the last years for kanamycin detection in milk samples [ 24 , 63 , 219 , 220 ]. A disposable, label-free aptasensor was developed by Sharma et al by employing diazonium chemistry for the aptamer immobilization.…”
Section: Electrochemical Aptasensors Developed Using Aryldiazonium Chemistry For Food Safety Monitoring Applicationsmentioning
confidence: 99%
“…Electrochemical sensor has been identified as one of the most feasible methods for the detection of heavy metal, for the devices are not only low-cost and relatively simple but have also high selectivity and sensitivity [ 20 , 21 ]. Moreover, a series of nanomaterials have been used in analytical electrochemistry, including gold nanoparticles [ 22 , 23 , 24 ], metal or metal oxide nanoparticles [ 25 , 26 ], quantum dots [ 11 ], graphene [ 14 , 27 ], and metal–organic frameworks (MOFs) [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%